EFFECT OF ULTRAVIOLET RADIATION (UVR) ON THE TROPICAL MICROALGA Chlorella vulgaris - C.Y., Wong; M.L., Teoh; S.M., Phang; W.L, Chu (Malaysian Journal of Science, 2011)
The effect of ultraviolet radiation (UVR) on the growth, lipid content and fatty acid profile of the tropical microalga Chlorella vulgaris UMACC 001 was investigated under laboratory and natural UVR conditions. The Chlorella was exposed to 10 days of PAR+UVA+UVB (1.17 Wm-2 ), PAR+UVA (8.54 Wm-2 ) and PAR alone (42 Âµmolm -2 s -1 ) in the laboratory study. The natural UVR study was carried out by exposing the cultures to the natural environment on the roof-top of the Institute of Graduate Studies Building, University of Malaya for 54 hours. The average levels of UVA radiation, UVB radiation and PAR irradiance over the exposure period ranged from 3.66 to 27.95 Wm-2 , 1.61 to 16.50 Wm- 2 and 282 to 1480 Âµmol m -2 s -1 , respectively. UVA radiation did not affect the growth of Chlorella vulgaris UMACC 001 in both the laboratory and natural UVR studies. In contrast, growth was adversely affected by UVB radiation in the laboratory study. UVB radiation is known to decrease the stability of D1 protein (the herbicide binding protein of chloroplasts) of the photosystem II reaction centre (PSII), affect rubisco activity, pigment composition as well as generate superoxide dismutase, all of which would reduce photosynthesis and growth. No significant difference was observed in the lipid content of the cultures exposed to UVR compared to PAR alone in both laboratory and roof-top (natural UVR) cultures. Chlorella vulgaris UMACC 001 exhibited different response in fatty acid profiles under laboratory condition compared to roof-top (natural UVR) cultures. In the laboratory condition, more saturated fatty acids (SFA) were produced in the cultures exposed to laboratory-produced UVB radiation compared to PAR alone, while more polyunsaturated fatty acids (PUFAs) were produced in the cultures exposed to natural UVB radiation compared to PAR alone